Triethyl-Borates as Surfactants to Stabilize Semiconductor Nanoplatelets in Polar Solvents and to Tune Their Optical Properties - Deng, Yalei; Chen, Xufeng; Liang, Jing; Wang, Yuanyuan (Frontiers in Chemistry, 2022)
Stabilizing nanocrystals (NCs) with high fluorescence quantum efficiency in suitable solvents and tuning of their optical properties precisely is critical for designing and assembling optoelectrical devices. Here, we demonstrated that by replacing the original X-type ligand (R-COO-) with triethyl-borate (TEB), zinc-blend structure nanoplatelets (Zb-NPLs) turn from hydrophobic to hydrophilic and are quite stable in polar solvents. More importantly, a large shift of 253 meV is observed for the TEB-passivated NPLs that can be attributed to the strain of the crystal lattice and the delocalizing of electron or hole to the ligand shell. It is worth noting that unlike conventional inorganic ligands, such as metal chalcogenide complexes or halides that quench fluorescence, TEB-treated NPLs maintain 100% of their original brightness in polar solvents with a slight increase in full width at half maximum (FWHM, 32 nm). Furthermore, we explore the possibility of employing TEB as surface ligands for NPLs with different thickness and compositions. We believe the discovery of new surface chemistry using borate related ligands can greatly expand the potential application areas of NPLs.